Kinerja Tradisi Muludan Endog-Endogan: Refleksi Ajaran Islam dan Budaya Lokal pada Masyarakat Banyuwangi: The Practice of the Muludan Endog-Endogan Tradition: A Reflection of Islamic Teachings and Local Culture in the Banyuwangi Community - Syamsudini Syamsudini (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2009)
The adaptation between humans and their natural environment continuously produces local cultural traditions, yet such traditions often face tension between preservation and accusations of religious deviation. This study is situated within the theoretical framework of Islam-local culture acculturation, exploring how Islamic teachings interact with and are reflected in indigenous rituals. The research aims to analyze the historical process, underlying preservation factors, and specific activities of the Muludan Endog-Endogan tradition in Banyuwangi, East Java. Employing a qualitative ethnographic approach, the study utilized participant observation, in-depth interviews with key informants including cultural figures and religious leaders, and extensive document review. The findings reveal that this tradition, characterized by decorated eggs (endog-endogan) and ceremonial processions (kirab jodang), emerged post-Blambangan kingdom era as a creative initiative to enliven the Prophet Muhammad’s birthday. Its persistence is driven by religious motivation based on hadith, a sense of pride and social prestige among hosts, and the collective belief in acquiring divine blessings (barokah). The study concludes that Muludan Endog-Endogan represents a dynamic local Islamic tradition that successfully synthesizes devotional piety with cultural expression. It is recommended that such traditions be supported as living heritage, while ensuring that the core veneration of the Prophet remains free from cultic exaggeration. Adaptasi antara manusia dan lingkungan alamnya terus menerus menghasilkan tradisi budaya lokal, namun tradisi semacam ini sering menghadapi ketegangan antara upaya pelestarian dan tuduhan penyimpangan agama. Penelitian ini berada dalam kerangka teori akulturasi Islam dan budaya lokal, serta mengeksplorasi bagaimana ajaran Islam berinteraksi dengan dan direfleksikan dalam ritual pribumi. Penelitian ini bertujuan menganalisis proses sejarah, faktor pendorong pelestarian, dan kegiatan spesifik dari tradisi Muludan Endog-Endogan di Banyuwangi, Jawa Timur. Dengan menggunakan pendekatan etnografi kualitatif, penelitian ini menerapkan observasi partisipan, wawancara mendalam dengan informan kunci termasuk tokoh budaya dan tokoh agama, serta kajian dokumen yang ekstensif. Temuan penelitian mengungkapkan bahwa tradisi yang bercirikan telur hias (endog-endogan) dan arak-arakan (kirab jodang) ini muncul pasca era kerajaan Blambangan sebagai inisiatif kreatif untuk meramaikan peringatan kelahiran Nabi Muhammad. Kelestariannya didorong oleh motivasi religius berdasarkan hadis, rasa bangga dan peningkatan status sosial tuan rumah, serta keyakinan kolektif akan perolehan berkah ilahi (barokah). Penelitian menyimpulkan bahwa Muludan Endog-Endogan merupakan tradisi Islam lokal dinamis yang berhasil mensintesis kesalehan devotional dengan ekspresi budaya. Direkomendasikan agar tradisi semacam ini didukung sebagai warisan hidup, sembari memastikan bahwa pemuliaan inti kepada Nabi tetap bebas dari pemujaan berlebihan.